ANALISIS KESALAHAN BERBAHASA PADA ARTIKEL ILMIAH MAHASISWA SEMESTER IV PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNDANA - Nitbani, Semuel H. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study aims to describe the use of diction and sentence writing in scientific articles of Indonesian Language and Literature Education Study Program students. This research is classified as descriptive qualitative research. The object of this research is student writing in the form of scientific articles of fourth semester students of Indonesian Language and Literature Education Study Program with data and data sources in the form of Scientific Writing Course assignments. The data were collected using documentary study, then analyzed using descriptive qualitative technique. The results of the study explain that the errors contained in the students' scientific articles consist of errors in the use of diction resulting in ambiguous sentences and the use of sentences that are not cohesive.